The evaluation system of ecological and low-carbon village in Zhejiang Province - X. Y. Luo; J. Ge; M. Y. Lu (Lowland Technology International, 2015)
This study constructed the evaluation system frame of ecological and low-carbon Village through 6 factors which are plan management, Eco-environment, Infrastructure, economics, energy saving and characteristic appearance in terms of the village attributes in Zhejiang Province . As well as the weight coming from the AHP method, and the judging method with the unity of the subjective and objective, a whole evaluation system has been made. This research chooses 2 different classic villages in Zhejiang Province as a case study and uses the above evaluation system to analyze and evaluate them, which verifies the feasibility of the evaluation system. We hope our study can promote the construction of the ecological and lowcarbon Village and give some reference to the village development in Zhejiang Province and even to the whole country